1992
DOI: 10.1042/bj2880123
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C phosphorylation of cardiac troponin T decreases Ca2+-dependent actomyosin MgATPase activity and troponin T binding to tropomyosin-F-actin complex

Abstract: Effects of phosphorylation of bovine cardiac troponin T (TnT) by protein kinase C on the Ca(2+)-stimulated MgATPase activity of reconstituted actomyosin complex and the binding of TnT to tropomyosin(Tm)-F-actin were investigated. The Ca(2+)-stimulated MgATPase of actomyosin containing phosphorylated TnT (1.8 mol of P/mol), compared with that containing unphosphorylated TnT, was decreased by up to 48%. Phosphorylation of TnT also decreased (up to 48%) its maximum binding to Tm-F-actin, which was accompanied by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 65 publications
2
47
0
Order By: Relevance
“…Phosphorylation of CTnT in rat cardiomyocytes with PKC isozymes alpha, delta, and epsilon at T190, S194, T199, and T280 led to decreased Ca 2+ sensitivity and activity of MgATPase, whereas phosphorylation by PKC-zeta resulted in a slight increase of the Ca 2+ sensitivity without affecting the maximal activity of MgATPase (74). Moreover, phosphorylation of bovine CTnT decreased (up to 48%) its maximum binding to Tm-actin, which was accompanied by a decrease (up to 3.5-fold) in its apparent binding affinity (75). Similarly to CTnI, phosphorylation of CTnT affect the function of the thin filament and its interaction with the thick filament in vitro but the physiological significance of these processes in vivo is still not well understood.…”
Section: Troponin Tmentioning
confidence: 98%
“…Phosphorylation of CTnT in rat cardiomyocytes with PKC isozymes alpha, delta, and epsilon at T190, S194, T199, and T280 led to decreased Ca 2+ sensitivity and activity of MgATPase, whereas phosphorylation by PKC-zeta resulted in a slight increase of the Ca 2+ sensitivity without affecting the maximal activity of MgATPase (74). Moreover, phosphorylation of bovine CTnT decreased (up to 48%) its maximum binding to Tm-actin, which was accompanied by a decrease (up to 3.5-fold) in its apparent binding affinity (75). Similarly to CTnI, phosphorylation of CTnT affect the function of the thin filament and its interaction with the thick filament in vitro but the physiological significance of these processes in vivo is still not well understood.…”
Section: Troponin Tmentioning
confidence: 98%
“…In skinned skeletal muscle fibers, RLC phosphorylation increases sensitivity to activating Ca 2ϩ such that there is a significant leftward shift in the force-Ca 2ϩ relationship (4 -6). Increased RLC phosphorylation in skeletal muscle is also associated with potentiation of isometric twitch tension with repeated activation and inactivation of contraction (7,8), rate of force production (9 -11), and maximum Ca 2ϩ -stimulated MgATPase activity (12). The mechanistic basis for the effects of RLC phosphorylation in striated muscle is hypothesized to be a lessening of the weak interaction of the myosin head with the myosin backbone and is probably due to a net charge change in a critical region of the protein (13).…”
mentioning
confidence: 99%
“…However, under the latter conditions, both cTnI and cTnT were phosphorylated (Noland and Kuo 1991). An additional study indicated that PKCmediated phosphorylation of cTnT lowered the apparent affinity for binding tropomyosin(Tm)-F-actin, which correlated with the inhibition of Ca 2+ -stimulated actomyosin MgATPase activity (Noland and Kuo 1992). A more direct study in which transgenic mice lacking PKC phosphorylation sites expressed approximately 50% fast skeletal TnT (fsTnT) provided evidence for a potential role of cTnT phosphorylation in depressing/reducing myofilament force (Montgomery et al 2001).…”
Section: Ser275mentioning
confidence: 99%